Human Acid-Labile Subunit Deficiency: Clinical, Endocrine and Metabolic Consequences - Domene, Horacio Mario (2009)
The majority of insulin-like growth factor (IGF)-I and IGF-II circulate in the serum as a complex with the insulin-like growth factor binding protein (IGFBP)-3 or IGFBP-5, and an acid-labile subunit (ALS). The function of ALS is to prolong the half-life of the IGF-I-IGFBP-3/IGFBP-5 binary complexes. Fourteen different mutations of the human IGFALS gene have been identified in 17 patients, suggesting that ALS deficiency may be prevalent in a subset of patients with extraordinarily low serum levels of IGF-I and IGFBP-3 that remain abnormally low upon growth hormone stimulation. Postnatal growth was clearly affected. Commonly, the height standard deviation score before puberty was between –2 and –3, and approximately 1.4 SD shorter than the midparental height SDS. Pubertal delay was found in 50% of the patients. Circulating IGF-II, IGFBP-1, -2 and -3 levels were reduced, with the greatest reduction observed for IGFBP-3. Insulin insensitivity was a common finding, and some patients presented low bone mineral density. Human ALS deficiency represents a unique condition in which the lack of ALS proteins results in the disruption of the entire IGF circulating system. Despite a profound circulating IGF-I deficiency, there is only a mild impact on postnatal growth. The preserved expression of locally produced IGF-I might be responsible for the preservation of linear growth near normal limits.